EKSPLORASI PEMBELAJARAN BIOLOGI MELALUI MORFOLOGI TUMBUHAN DIKOTIL DAN MONOKOTIL: MENGEMBANGKAN RASA INGIN TAHU DAN KRITIS DI LINGKUNGAN KAMPUS STKIP MELAWI PERBATASAN ENTIKONG - Nita Astuti; Azamul Fadhly Muhammad; Samsul Bahri (STKIP Subang, 2025)
This study aims to explore biology learning through the observation of the morphology of dicot and monocot plants as an effort to foster the curiosity and critical attitude of students in the STKIP Melawi campus environment, Entikong border area. The method used is field observation which is carried out directly in the environment around the campus. Students systematically recorded morphological data using observation tables, including the structure of roots, stems, leaves, flowers, and seeds. In addition, reflective question sheets are given to explore students' conceptual understanding and scientific attitudes. The results of the observation showed that students were able to identify the difference in morphological characteristics between dicot and monocot plants precisely. This activity encourages active, contextual learning, and strengthens mastery of concepts through hands-on experience. These findings show that the exploration of plant morphology is effective in increasing the learning interest and critical thinking skills of biology students.